Where Did All the Borrowing Go? : A Forensic Analysis of the U.S. External Position - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper ;, 2008)
The deterioration in the U.S. net external position in recent years has been much smaller than the extensive net borrowing associated with large current account deficits would have suggested. This paper examines the sources of discrepancies between net borrowing and accumulation of net liabilities for the U.S. economy over the past 25 years. In particular, it highlights and quantifies the role played by net capital gains on the U.S. external portfolio and 'residual adjustments' in explaining this discrepancy. It discusses whether these 'residual adjustments' are likely to be originating from measurement errors in external assets and liabilities, financial flows, or capital gains, and explores the implications of these conjectures for the U.S. financial account and external position.